How successful is grassland restoration after removal of pine plantations on the eastern shores of Lake St Lucia? - Zaloumis, Nicholas Paul (Department of Biological Sciences, 2017)
The coastal grasslands that occur along the Eastern Shores of Lake St. Lucia are rich in plant species, including endemics. These grasslands in North KwaZulu-Natal, South Africa, are remnants of a severely threatened vegetation type. Large portions of the Eastern Shores have been utilized for commercial pine plantations over the last 50 years; however these have been removed over the last 17 years. It is therefore important that efforts to restore grasslands that have been previously afforested stands of pines are successful. These grassland systems are fire driven and therefore many plants have adapted to these conditions by having massive storage organs below the ground. Using several response variables I was able to assess the effects of plantations on alpha- and beta-diversity and functional traits of forb and other grassland species and attempted to determine whether these disturbed grassland were returning to their original state. A high level of community heterogeneity was found at both scales for natural vegetation, while more homogenous, species low patterns were seen in post-plantation sites. Most notable was the large number of missing resprouting species in pine sites and that, in contrast to forest rehabilitation studies, no evidence for succession was found. The implication of this is massive as grassland rehabilitation may be a lot harder than was previously thought. It is likely that the fire adapted forb species are bad colonizers and have struggled to return to disturbed sites. These grasslands are therefore susceptible to activities that remove or eliminate the considerable amount of below ground biomass from the soil, and these sorts of disturbances should be avoided. Active rehabilitation methods will be required if any progress is going to be made and until such methods are effective considerable effort should be made in conserving the remaining grasslands that we have left and promoting its pharmaceutical, horticultural and societal value.